ST–Segment elevation: Not always an acute coronary syndrome - Érico Costa; Elsa Meireles; Catarina Rodrigues; Tiago Godinho Teixeira; Dulce Silva (Publisher: Shahid Beheshti University of Medical Sciences, 2017)
Cardiac tumors can be primary or metastatic, the latter being more frequent and usually of pulmonary or hematologic origin. These patients’ clinical signs are non-specific and the electrocardiogram (ECG) can assume many patterns, among which, ST-segment elevation. Nevertheless, associated occlusion of the coronary arteries is rare in these situations.We present a 79-year-old woman with a history of pulmonary neoplasia who was admitted to the emergency department due to atypical chest pain, cough and worsening dyspnea in the previous 3 days. The ECG revealed an ST-segment elevation in the anterolateral and inferolateral leads, despite normal blood work, namely normal troponin. Due to the disparity between the patient’s symptoms and the ECG findings, a decision was made not to proceed to primary angioplasty, but to further investigate with echocardiography, which revealed a mass localized in the anterolateral and inferolateral left ventricle walls, confirmed by computed tomography. The patient was admitted in the medical ward for symptomatic management. Her clinical condition gradually deteriorated due to the disease’s natural evolution and she died two weeks later.This case highlights the importance to keep in mind differential diagnoses to acute coronary syndromes, when a ST-segment elevation is encountered on an ECG.